Regulating the regulatory T cells as cell therapies in autoimmunity and cancer - Hosseinalizadeh, Hamed; Rabiee, Fatemeh; Eghbalifard, Negar; Rajabi, Hamid; Klionsky, Daniel J.; Rezaee, Aryan (Frontiers in Medicine, 2023)
Regulatory T cells (Tregs), possess a pivotal function in the maintenance of immune homeostasis. The dysregulated activity of Tregs has been associated with the onset of autoimmune diseases and cancer. Hence, Tregs are promising targets for interventions aimed at steering the immune response toward the desired path, either by augmenting the immune system to eliminate infected and cancerous cells or by dampening it to curtail the damage to self-tissues in autoimmune disorders. The activation of Tregs has been observed to have a potent immunosuppressive effect against T cells that respond to self-antigens, thus safeguarding our body against autoimmunity. Therefore, promoting Treg cell stability presents a promising strategy for preventing or managing chronic inflammation that results from various autoimmune diseases. On the other hand, Tregs have been found to be overactivated in several forms of cancer, and their role as immune response regulators with immunosuppressive properties poses a significant impediment to the successful implementation of cancer immunotherapy. However, the targeting of Tregs in a systemic manner may lead to the onset of severe inflammation and autoimmune toxicity. It is imperative to develop more selective methods for targeting the function of Tregs in tumors. In this review, our objective is to elucidate the function of Tregs in tumors and autoimmunity while also delving into numerous therapeutic strategies for reprogramming their function. Our focus is on reprogramming Tregs in a highly activated phenotype driven by the activation of key surface receptors and metabolic reprogramming. Furthermore, we examine Treg-based therapies in autoimmunity, with a specific emphasis on Chimeric Antigen Receptor (CAR)-Treg therapy and T-cell receptor (TCR)-Treg therapy. Finally, we discuss key challenges and the future steps in reprogramming Tregs that could lead to the development of novel and effective cancer immunotherapies.